Evaluation of the efficacy and safety of photodynamic therapy using liquid crystal-loaded methylene blue and intense pulsed light in treatment of vitiligo - Manal M. Abdel-Monem; Amany M. Abdel-Latif; Gamal M. El Maghraby; Esraa E. Elhawary (Journal of the Egyptian Women's Dermatologic Society, 2026)
Background Depigmented macules and patches characterize vitiligo, an acquired autoimmune skin condition that has several lines of treatment. A new treatment for vitiligo, photodynamic therapy (PDT), has mixed results. Objective To evaluate the efficacy and safety of PDT using liquid crystal-loaded methylene blue and intense pulsed light in the treatment of vitiligo. Patients and methods This prospective, randomized study was conducted in 40 patients with multiple vitiligo lesions. For each patient, three vitiligo lesions were treated: Treatment area A was exposed to PDT alone (for six sessions at 2 weeks intervals), treatment area B was exposed to PDT and topical daily steroids (mometasone furoate cream) and treatment area C was exposed to only topical steroids (mometasone furoate cream) daily. There were two methods used to evaluate the repigmentation: a mean improvement score by physician carried out by three blinded dermatologists, and patients’ satisfaction. Results Improvement and its percentage were significantly higher in treatment area B compared with areas A and C, and were significantly higher in treatment area C compared with area A ( P